Perbandingan Minat Gadai Emas di Bank Syariah dan Pegadaian Syariah pada Masyarakat Kota Jambi - Mariyantizka, Viola; Habriyanto, Habriyanto; Martaliah3, Nurfitri (YASIN, 2024)
In an interview conducted with Mr. Abdi, he stated that in the midst of the current economic crisis, pawning gold was indeed a profitable business because many people carried out this practice. The price of gold on the market experienced a significant and rapid increase, reaching around Rp. 1,131,823 per gram. The aim is to analyze the comparison of the estimated value of gold at Islamic banks and Islamic pawnshops and to analyze the similarities and differences in gold pawning transactions at Islamic banks and Islamic pawnshops. This research uses qualitative methods which aim to understand the phenomena experienced by research subjects by collecting data in the form of words and not numbers. The results in this research are a realistic picture, information based on facts obtained by researchers in the field. Researchers conducted a survey at the research location using interviews, documentation and observation of research subjects designated as informants in this research. So researchers can draw the conclusion that there is a difference in public interest in pawning gold at Bank Syariah Indonesia and Pegadaian Syariah. Input for Sharia Banks and Pegadaian Syariah in improving the quality of sharia gold pawn products, both operational systems and services. So that people can continue to get the best service from Sharia Banks and Sharia Pegadaian.